Pendekatan Deep Learning pada Pembelajaran IPAS Berbasis Keterampilan Berpikir Kritis Siswa di Madrasah Ibtidaiyah - Anam, Isnaini; Muttaqin, Muhammad Fauzan; Amrina, Pebrisa (Jurnal Pendidikan Madrasah, 2026)
The low level of students’ critical thinking skills in Natural and Social Sciences (IPAS) learning remains a challenge in elementary education, particularly due to the predominance of teacher-centered instructional practices. This condition limits students’ active engagement and hinders the development of critical thinking abilities. This study aims to describe the implementation of the deep learning approach in IPAS learning as an effort to foster critical thinking skills among third-grade students at an Islamic elementary school (Madrasah Ibtidaiyah). The study employed a qualitative method with a case study approach conducted at MI Nurul Falah. Data were collected through participatory observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation. The findings indicate that the implementation of deep learning through exploration, discussion, and hands-on activities enhanced student engagement, deepened conceptual understanding, and promoted critical thinking skills. Students demonstrated improved abilities in identifying problems, analyzing information, expressing opinions, and drawing conclusions. Furthermore, the approach facilitated transfer of learning, enabling students to connect academic concepts with real-life situations. Therefore, deep learning is an effective approach for creating meaningful, active, and student-centered learning environments.